Development of Synthetic Ca-based CO2 Sorbents for Sorption Enhanced Reforming Coupled to Ca/Cu Chemical Loop. (July 2017) - López, J.M.; Navarro, M.V.; Murillo, R.; Grasa, G.S.
Abstract: Sorption Enhanced Reforming (SER) is a very promising option that allows H2 production coupled with capturing CO2 by sorption. The present research work focus in the sorbent point of view and several synthetic materials with a high CO2 absorption capacity and chemically and mechanically stable during multi-cyclic operation (at least 40 calcination-carbonation cycles and 100 cycles in some cases) under the typical SER process conditions have been developed. Two different synthesis routes (co-precipitation and mechanical mixing) have been followed trying to evaluate the effect of two different inert supports (magnesium oxide and mayenite) on the evolution of the CO2 carrying capacity of the materials. Also, sorbents have been synthesized with different morphologies (powder and particles) and sizes (from 100 microns up to 2 mm) in order to test their reactivity and mechanical suitability for large scale reactor system operation. Synthetic dolomite with a molar CaO/MgO ratio of 2:1 synthesized by co-precipitation method exhibited very stable performance for 100 consecutive carbonation/calcination cycles and a residual CO2 carrying capacity of 0.29 grCO2 /grcalcined sorbent . Also a very promising result has been obtained for this sorbent mixed with a commercial catalyst in a preliminary SER experiment that yield a H2 production of 92% vol. (d.b.).